2017
DOI: 10.1590/0037-8682-0429-2016
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of quality of life domains in patients with compensated Chagas heart failure after participating in a cardiac rehabilitation program

Abstract: The cardiac rehabilitation program significantly improved the physical quality of life of patients with Chagas heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 12 publications
2
16
0
3
Order By: Relevance
“…Therefore, we can suggest that physically active individuals could maintain sufficient levels of mobility and independence that positively influenced the perception of QoL in this domain. Thus, physical activity programs for patients with CD should be encouraged whenever individuals do not present medical restrictions .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we can suggest that physically active individuals could maintain sufficient levels of mobility and independence that positively influenced the perception of QoL in this domain. Thus, physical activity programs for patients with CD should be encouraged whenever individuals do not present medical restrictions .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that heart rate (beats per minute) in T. cruzi experimentally infected dogs was significantly higher than control dogs during acute infection, but no difference was found during the indeterminate phase [33]. Chronic Chagas cardiomyopathy in humans can cause a decreased response to exercise and stress due to failure of cardiac compensation [61,62]. However, benefits of exercise training in chronic heart failure patients has been shown, and new research suggests that regular exercise could assist with cardiac function in chronic Chagas disease in humans [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…30 Um programa de reabilitação cardíaca composto do mesmo protocolo de TEF mencionado acima, com TR e alongamentos, orientação nutricional adicional e aconselhamento farmacológico para pacientes com DC, demonstrou aumento da capacidade funcional e física, melhorando a qualidade de vida de pacientes chagásicos. 31 Em outro estudo importante, os pesquisadores realizaram TEF três vezes por semana em pacientes chagásicos. Eles demonstraram que o grupo que realizou exercícios aumentou o consumo de oxigênio de pico durante o exercício e a ventilação máxima por minuto, melhorando a capacidade funcional desses pacientes.…”
Section: Doença De Chagas E Treinamento Com Exercício Físico: Mirnas Como Possíveis Moduladoresunclassified